The Impact of Dow Jones Sustainability Index on US Dollar Value - Giannarakis, Grigoris; Garefalakis, Alexandros; Lemonakis, Christos; Sariannidis, Nikolaos (International Journal of Economics and Financial Issues, 2017)
The scope of this study is to address the impact of stock index returns on exchange rate. In particular, it aims to fill the literature gap regarding the determinant role of socially responsible companies on the exchange rate Trade Weighted U.S. Dollar Index to Major Currencies as a proxy for US dollar value. For this reason, the Dow Jones Sustainable Index World (DJSIW) as a proxy for the world’s leading companies in terms of economic, environmental and social criteria. A generalized autoregressive conditional heteroskedasticity (GARCH) model is employed over US dollar value to major currencies for the period January, 1999 to May, 2016 using monthly data. A number of control variables were introduced in the proposed model, namely Oil prices, US interest rate, US supply money, trade balance and consumer confidence. The empirical results revealed the negative impact of stock returns of socially responsible companies on US dollar value inconsistent with proposed empirical literature. The results have significant implications for investors, portfolio managers and policymakers hedging on diversification strategies for their portfolios. Keywords: Exchange Rate, Dow Jones Sustainability Index, Returns JEL Classifications: G1, F2, Q40, M21